Effectiveness of questionnaires for screening hearing of school-age children: A comprehensive literature review. (December 2014) - Muñoz, Karen; Caballero, Ana; White, Karl
Abstract Objective: The purpose of this study was to review the literature on the effectiveness of parent or teacher-completed questionnaires as a tool to screen school-aged children for permanent hearing loss. Design: A rapid evidence assessment was completed to provide a summary of information published between 1980 and 2013 in English or Spanish. To identify relevant publications, a database search was conducted using nine databases. Study sample: Seven studies were identified for inclusion in the review. Results: Authors of three of the studies recommended use of the questionnaire as a method for screening hearing in school-aged children, and authors of four of the studies did not recommend use of the questionnaire. However, only one of the seven studies provided good evidence that questionnaires are an effective way of identifying hearing loss among children. Conclusions: There is insufficient evidence that parent or teacher completed questionnaire screening can be reliably used to identify children in need of further hearing assessment. It is clear that more research is needed before concluding that questionnaires are an effective and low-cost tool for use to screen children for permanent hearing loss.